2004
DOI: 10.1002/micr.20058
|View full text |Cite
|
Sign up to set email alerts
|

Two applications of end‐to‐side nerve neurorrhaphy in severe upper‐extremity nerve injuries

Abstract: End-to-side and side-to-side techniques (what we call alternative nerve repair techniques) have been investigated in detail in both experimental and clinical studies. There have not been any large series, but only some case reports describing either successful or disappointing functional results in the recent literature. Two cases presented here were of two extreme examples of nerve injuries that had no chance for direct repair; alternative choices were performed. One was a side-to-side neurorrhaphy between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 18 publications
1
24
0
6
Order By: Relevance
“…This conformed previous findings by Luo et al [30]. Improvement in protective sensibility was also demonstrated by some authors performing median to ulnar end-to-side coaptation in several cases reported in the literature with long nerve defects [3134]. In such cases only partial motor recovery was occasionally seen.…”
Section: Clinical Applicationssupporting
confidence: 91%
“…This conformed previous findings by Luo et al [30]. Improvement in protective sensibility was also demonstrated by some authors performing median to ulnar end-to-side coaptation in several cases reported in the literature with long nerve defects [3134]. In such cases only partial motor recovery was occasionally seen.…”
Section: Clinical Applicationssupporting
confidence: 91%
“…Impairment of the donor nerve was observed in one case. Yüksel et al (2004) presented two cases with severe upper extremity nerve injuries. One patient underwent a side-to-side neurorrhaphy between the ulnar and median nerves, and the other end-to-side neurorrhaphy of the median and radial nerves to the ulnar nerve.…”
Section: Clinical Applicationsmentioning
confidence: 98%
“…Kayikçioglu et al 10 had no satisfying result at 21 months of followup. Yüksel et al 11 described diminished protective sensation recovery. Kostakoglu et al 8 sutured the median to the ulnar nerve with an end-to-side coaptation in the forearm.…”
Section: Discussionmentioning
confidence: 97%